The East Asian miracle: (D.C. : World Bank, 1993)
The extraordinary growth enjoyed over the last several decades by many East Asian countries has amounted to nothing less than an economic miracle. Employing unorthodox policies, Hong Kong, Indonesia, Japan, Malaysia, the Republic of Korea, Singapore, Taiwan, and Thailand have all produced dramatic results with far-reaching improvements in human welfare and income distribution, leading many to ask whether a similar achievement can be duplicated elsewhere. Written for the nonspecialist, this World Bank Policy Research Report--the first in an important new series--discusses in detail the means by which these high-performing Asian economies (HPAEs) realized their staggering success between 1965 and 1990. Examining how these countries stabilized their economies with sound development programs that led to fast growth, the book also shows how they shared the new prosperity by making income distribution more equitable. The book makes clear how the HPAEs promoted rapid capital accumulation by making banks more reliable and encouraging high levels of domestic savings, while universal primary schooling and better primary and secondary education quickly increased their skilled labor forces. Also included are illustrative examples of productive agricultural programs, modest tax policies, the modification of price distortions, foreign technology and investment, and the cooperation of government and private enterprise.